Pengaruh Harga Dan Citra Merek Terhadap Minat Beli Wisatawan Domestik Di Pusat Oleh-Oleh Joger, Kuta, Bali - Jambak, Risa Kariba; Sukana, Made (JURNAL DESTINASI PARIWISATA, 2019)
The—development--of business today is increasingly complex. Everyday-people are involved in...business_activity such--as purchasing of merits and stuffes . In this era of globalization, the business competition _must be transparant and consistent in meeting the needs of consumers, beside they must -also compete with competitors to maintain the image of their consumers. This also applies to the tourism industry. One of the tourism industries engaged in goods and services is the business center for souvenirs (shopping tourism). Several things that items to be considered as business are factors that can influence the buying interest of tourists at the center of souvenirs. This study –aims- to –analyze- the _influence - of - price factors and brand image related to domestic tourist shopping interests at the Jogger souvenir center, Kuta, Bali. This study uses multiple regression analysis methods with data sourced from observations, interviews, questionnaires, documentation and literature studies with non-probability sampling techniques as a method of determining to sample. Based on this research it could be concluded by the _price factor and brand _image has a significant influences on the buyinginterest of domestictourists on Joger, Kuta, Bali. Keywords: Tourist Characteristics, Price, Brand Image, Purchase Interest, Joger Kuta.